EFFICIENCY IN INDUCTION MOTOR SPEED CONTROL: EXPLORING PWM AND PHASE ANGLE TECHNIQUES - Ezeh, Kelechi O.; Nwankwo, Ifeoma A (Research Journal of Engineering and Allied Sciences, 2024)
In this research, the speed control of induction motor using PWM and Phase angel controlling techniques was investigated under the following conditions. In the first stage, the induction motor was operated at a speed set point of 2830 RPM and with rated torque 10Nm. While in the second part, the induction motor was operated at 50% of the rated set point speed of 1415 RPM and 50% of the rated torque (5Nm). The result shows that PWM and phase angle controllers exhibited varying degrees of high efficiency in the reduction of speed overshoot and settling time. From the performance improvement of the simulation carried out, the PWM controller reduced the speed response overshoot and settling time of the phase angle controller by 1.51% and 13.51% respectively for the reference speed set point of 2830 RPM and torque of 10NM. But for the case of 50% of these rated parameters of speed set point and torque, the reduction in speed overshoot and settling time of phase angle controller by the PWM are 15.11% and 13.64% respectively. This implies that the speed control under PWM leads in efficiency of machine operations and effective energy utilization.